2017
DOI: 10.1016/j.jneb.2017.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Feeding and Mealtime Correlates of Maternal Concern About Children's Weight

Abstract: Objective Examine differences within two domains of weight-related parenting: child feeding practices and family meal characteristics, among mothers of young children by concern about children becoming overweight. Design Cross-sectional study Participants Low-income mothers (N=264, 67% non-Hispanic white) and their children (51.5% male, age range: 4.02 – 8.06 years). Variables measured Maternal concern and feeding practices were measured using the Child Feeding Questionnaire (CFQ). Meal characteristics w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
12
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 31 publications
5
12
1
1
Order By: Relevance
“…Compared to those who were not concerned about their child’s weight or their children’s eating, we found that mothers who reported being concerned about their children’s weight or eating reported higher levels of controlling, parent-led feeding practices. These results support previous research that found mothers’ concern about children’s weight resulted in more frequent use of pressure to eat [ 11 , 21 ] and restrictive feeding practices [ 11 , 12 , 22 ]. In their longitudinal study with over 4800 children, Jansen and colleagues also found that when mothers perceived that their child ate very little they pressured their child to eat more [ 23 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Compared to those who were not concerned about their child’s weight or their children’s eating, we found that mothers who reported being concerned about their children’s weight or eating reported higher levels of controlling, parent-led feeding practices. These results support previous research that found mothers’ concern about children’s weight resulted in more frequent use of pressure to eat [ 11 , 21 ] and restrictive feeding practices [ 11 , 12 , 22 ]. In their longitudinal study with over 4800 children, Jansen and colleagues also found that when mothers perceived that their child ate very little they pressured their child to eat more [ 23 ].…”
Section: Discussionsupporting
confidence: 90%
“…This suggests that concern about child’s weight does not appear to translate into mothers engaging in health promoting parenting practices regarding child physical activity. While some researchers have argued that identification of their child’s weight as a problem is a prerequisite to parental behaviour change [ 25 28 ], our findings as well as those from previous research [ 12 , 29 ], suggest that parental concern about their child’s weight does not lead to health promoting weight-related parenting practices. Among a sample of 314 American parents (92% mothers), those who recognized that their child was overweight or obese were no more likely to engage in health promoting parenting practices, such as increasing access to healthful foods or encouraging their child to be physically active, than parents who did not recognize their child was overweight or obese [ 29 ].…”
Section: Discussionsupporting
confidence: 48%
“…Preocupación por el peso del niño: Respecto a la preocupación por el peso del niño, se cuenta con evidencia que apunta a que padres preocupados por el peso de sus hijos controlarían su alimentación o desarrollarían prácticas restrictivas, en un intento de evitar que el niño presente sobrepeso 12,25,27,28 . También ha sido asociada a monitoreo de la alimentación y presión para comer 27 , y a conductas como limitar tiempo frente a pantallas, implementar mejoras en la dieta, aumentar la actividad física 26 y reducir ingesta de alimentos 27 .…”
Section: Actitudes Parentales Hacia La Alimentación Infantil Referenciaunclassified
“…Maternal concerns alone may not be su cient to motivate actions to reduce the risks of childhood obesity [21]. In 2010, Webber et al used CFQ to con rm the impact of maternal perceptions and concerns on the weight status of their children [20].…”
Section: The Association Between Caregivers' Feeding Behavior and Chimentioning
confidence: 99%
“…At present, most studies have reported on associations between caregivers' feeding behavior, children's eating behavior, and body weight based on samples from European 12, [20] and North American populations [21,22], and food-related caregivers' feeding behavior, children's eating behavior have shown great variations according to demographic characteristics [19,23]. The association among caregivers' feeding behavior, their children's eating behavior and body weight might be different in China and other countries, and this association, particularly in Chinese children of preschool age preschooler, has not been well studied in China.…”
Section: Introductionmentioning
confidence: 99%